Analysis of Factors Influencing Turnover Intention of Go Online’s Employees - Didin Hikmah Perkasa; Ryani Dhyan Parashakti; Dinar Nur Affini; Nur Endah Retno Wuryandari; Leli Deswindi (Dinasti Publisher, 2023)
This research was conducted to determine the factors that influence turnover intention. In this case, the researcher wants to find out whether the variables being examined, namely compensation, work environment, and work stress, affect the turnover intention at Go Online. This research is expected to be able to provide a solution to the employees’ desire who will leave their jobs not to cause serious problems. If the company is able to handle it well, it will increase the productivity of the company. The objects of this study were 144 Go Online employees and the sample use the Slovin formula so the respondents studied were 88 people. The method used is causal quantitative descriptive, to determine the effect of the independent variable on the dependent variable. The data analysis used is statistical analysis in the form of multiple linear regression tests using an analytical tool of SPSS 23. Prior to the test, a validity test, and reliability test were carried out, followed by hypothesis testing. The results of this study indicate that the compensation variable has a negative effect on turnover intention, the work environment has a negative effect on turnover intention, and work stress has a positive effect on turnover intention at Go Online.